Elevated SRPK1 lessens apoptosis in breast cancer cells through RBM4-regulated splicing events - Lin, Jung-Chun; Lin, Ching-Yu; Tarn, Woan-Yuh; Li, Fang-Yu (RNA (Cambridge), 2014)
Imbalanced splicing of premessenger RNA is typical of tumorous malignancies, and the regulatory mechanisms involved in several tumorigenesis-associated splicing events are identified. Elevated expression of serine-arginine protein kinase 1 (SRPK1) may participate in the pathway responsible for the dysregulation of splicing events in malignant tumor cells. In this study, we observed a correlation between the cytoplasmic accumulation of RNA-binding motif protein 4 (RBM4) and up-regulated SRPK1 in breast cancer cells. The production of the IR-B and MCL-1 S transcripts was induced separately by the overexpression of RBM4 and SRPK1 gene silencing. Overexpressed RBM4 simultaneously bound to the CU-rich elements within the MCL-1 exon2 and the downstream intron, which subsequently facilitated the exclusion of the regulated exon. Breast cancer cells are deprived of apoptotic resistance through the RBM4-mediated up-regulation of the IR-B and MCL-1 S transcripts. These findings suggest that the splicing events regulated by the SRPK1-RMB4 network may contribute to tumorigenesis through altered sensitivity to apoptotic signals in breast cancer cells.